2022
DOI: 10.1101/2022.05.25.493488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Van Gogh/Vangl tyrosine phosphorylation switch regulates its interaction with core Planar Cell Polarity factors Prickle and Dishevelled

Abstract: Epithelial tissues can be polarized along two axes, in addition to apical-basal polarity they are often also polarized within the plane of the epithelium, known as planar cell polarity (PCP). PCP depends upon the conserved Wnt/Frizzled (Fz) signaling factors, including Fz itself and Van Gogh (Vang/Vangl). Here, taking advantage of the complementary features of Drosophila wing and mouse skin PCP establishment, we dissect how Vang phosphorylation on a specific conserved tyrosine residue affects its interaction w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…phosphorylation is a modest fraction of the total phosphorylation of Vang in vivo, making it difficult to detect. Treatment with the dual serine/threonine and tyrosine-specific lambda phosphatase reveals significant phosphorylation of Vang in vivo, and tyrosine phosphorylation of Vang has also been demonstrated (Humphries et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…phosphorylation is a modest fraction of the total phosphorylation of Vang in vivo, making it difficult to detect. Treatment with the dual serine/threonine and tyrosine-specific lambda phosphatase reveals significant phosphorylation of Vang in vivo, and tyrosine phosphorylation of Vang has also been demonstrated (Humphries et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…Of note, the MS analysis identified tyrosine phosphorylation (Y473) that was shown to be mediated by the Abl kinase and to have a relatively PCP‐specific requirement, as a Y473F mutant behaves much like the PCP‐specific dsh 1 allele (Singh et al , 2010; Yanfeng et al , 2011). Tyrosine phosphorylations have been proposed to regulate additional aspects of PCP signaling as well (Guo et al , 2013; Kelly et al , 2016; Humphries et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the MS analysis identified a tyrosine phosphorylation (Y473) that was shown to be mediated by the Abl kinase and to have a relatively PCP-specific requirement, as a Y473F mutant behaves much like the PCP-specific dsh 1 allele (Singh et al , 2010; Yanfeng et al ., 2011). Tyrosine phosphorylations have been proposed to regulate additional aspects of PCP signaling as well (Guo Zanetti & Schekman, 2013; Humphries et al , 2023; Kelly et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We, however, do not favor this possibility because 1) the binding between Pk and Dvl was reported to be quite weak (Bastock et al, 2003); 2) our unpublished data show that ΔPL, a Pk mutant lacking the PET/LIM domains necessary for Dvl binding (Takeuchi et al, 2003), can largely mimic wild-type Pk function. Furthermore, a new study in flies showed that the phosphorylation status of a conserved tyrosine in the cytoplasmic tail of Vang provides opposite binding preference for Pk and Dsh, suggesting that simultaneous binding of both Pk and Dsh to the C-terminus of Vang may not be possible (Humphries et al, 2023).…”
Section: Regulation Of Vangl-dvl Interaction By Pk To Suppress Non-ca...mentioning
confidence: 99%